Quality assurance and quality control for post-tensioned concrete structures (FIP guide to good practice., 1986)
This report deals with quality assurance and control in the construction of post-tensioned structures, with the aim to replace 'inspection for quality' with 'engineering for quality' Contents include organizations, pre-stressing, design procurement, construction planning and quality control.